The Effect of Geopedia Web-Based Learning on Students’ Spatial Thinking Skills in Geography Learning - Saiful Amin; Abdul Bashith; Muchammad Akbar Kurniawan; Sari Dewi; Muhammad Akmal Muzakki Dwi Syah Putra; Mahadir Muhammad Fikri Rohmatulloh (IAIN Madura, 2026)
The limited spatial thinking skills in students can be attributed to traditional geography instruction and the insufficient integration of technology-based learning tools. This research seeks to examine the impact of using Geopedia web media within web-based learning on students’ spatial thinking abilities, specifically regarding lithospheric materials, at MA Ahmad Yani Jabung, Malang Regency. This research employs a quantitative method with a quasi-experimental framework, utilizing a one-group pretest-posttest design on a sample of 23 eleventh-grade students. The research tool consists of a multiple-choice test that has undergone validity, reliability, discrimination, and difficulty testing, and was subsequently analyzed using the Paired Sample T-Test. According to the results, there was an increase in the mean spatial thinking ability of students, demonstrating a notable difference before and after the intervention. According to the discussion, Geopedia web media proves to be more effective in improving students' spatial thinking skills. This is because it delivers a learning experience that is more engaging, visually rich, and context-based, enabling students to understand spatial concepts in a more profound and applicable manner than conventional methods.